1976
DOI: 10.1093/infdis/134.3.271
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between Amikacin and Cefazolin against Klebsiella: In Vitro Studies and Effect on the Bactericidal Activity of Serum

Abstract: Synergism between amikacin and cefazolin was studied in vitro in 20 strains of Klebsiella isolated from clinical material. Several techniques for the demonstration of synergism in vitro were employed. The checkerboard technique with use of bactericidal end points and the killing curves method showed synergism between amikacin and cefazolin for 13 and 15 strains, respectively. The two techniques were in accordance in 12 instances. The data obtained in vitro were correlated with the bactericidal activity in sera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

1977
1977
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…On the other hand, several studies examining small numbers of strains have suggested rough correlations between results obtained by different methods (110,191). Klastersky et al (101) found agreement between time-kill and MBC checkerboard assessment of cefazolin-amikacin interactions for 60% (13 of 20) of Klebsiella isolates. Norden et al (141) illustrated discrepancies when various methods and criteria were applied in examining cephalothin-gentamicin interactions against Klebsiella, but, in general, synergism by MIC checkerboard testing did predict synergism by time-kill methods (although the reverse was not true).…”
Section: Correlation Of Results By Various Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, several studies examining small numbers of strains have suggested rough correlations between results obtained by different methods (110,191). Klastersky et al (101) found agreement between time-kill and MBC checkerboard assessment of cefazolin-amikacin interactions for 60% (13 of 20) of Klebsiella isolates. Norden et al (141) illustrated discrepancies when various methods and criteria were applied in examining cephalothin-gentamicin interactions against Klebsiella, but, in general, synergism by MIC checkerboard testing did predict synergism by time-kill methods (although the reverse was not true).…”
Section: Correlation Of Results By Various Methodsmentioning
confidence: 99%
“…Since that time, numerous studies utilizing various techniques and definitions have provided evidence for beta-lactam-aminoglycoside synergism against gram-negative bacilli (64). Although considerable attention has been given to the study of interactions against the Enterobacteriaceae (40,66,67,95,101), much attention has also been focused on activities of combination regimens against P. aeruginosa, no doubt due to difficulties in treating many such infections in seriously ill patients (19).…”
Section: Mechanisms Of Bactericidal Synergismmentioning
confidence: 99%
“…This may be one explanation of the discrepancies described by Norden et al (22). A few investigators have used the MBC to study antibiotic synergism (1,13,30).…”
mentioning
confidence: 99%
“…β-Lactam-aminoglycoside combination therapy was advocated long ago mainly because of an observation of synergy between these antibiotic classes in vitro, i.e. enhanced killing of bacteria in the plate or tube with the combination as compared to the sum of the individual activities of antibiotic constituents of the combination [2,3,4]. However, between the plate in the microbiology laboratory and the individual patient treated in the ward there is a huge gap.…”
Section: Asking the Right Clinical Questionmentioning
confidence: 99%